2023
DOI: 10.3390/pharmaceutics15030956
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Inhibition of Herpes Simplex Virus 1 Infection by Tricationic Amphiphilic Porphyrin with a Long Alkyl Chain

Abstract: Photodynamic therapy (PDT) is broadly used to treat different tumors, and it is a rapidly developing approach to inactivating or inhibiting the replication of fungi, bacteria, and viruses. Herpes simplex virus 1 (HSV-1) is an important human pathogen and a frequently used model to study the effects of PDT on enveloped viruses. Although many photosensitizers (PSs) have been tested for their antiviral properties, analyses are usually limited to assessing the reduction in viral yield, and thus the molecular mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…virals (Section 3.2), but it was later shown that the compounds act as membrane-targeted photosensitizers [491][492][493]. Cationic imidazolyl and pyridyl porphyrins were characterized as promising photosensitizing antivirals against SARS-CoV-2 and HSV-1 [494,495]. A natural chlorine photosensitizer, pheophorbide a, inactivates HSV-1, HSV-2, MERS-CoV, SARS-CoV-2, YFV, HCV, and SINV, by targeting the lipid envelope [496,497] (Table 7).…”
Section: Disrupting Agents 411 Photosensitizing Antiviralsmentioning
confidence: 99%
See 1 more Smart Citation
“…virals (Section 3.2), but it was later shown that the compounds act as membrane-targeted photosensitizers [491][492][493]. Cationic imidazolyl and pyridyl porphyrins were characterized as promising photosensitizing antivirals against SARS-CoV-2 and HSV-1 [494,495]. A natural chlorine photosensitizer, pheophorbide a, inactivates HSV-1, HSV-2, MERS-CoV, SARS-CoV-2, YFV, HCV, and SINV, by targeting the lipid envelope [496,497] (Table 7).…”
Section: Disrupting Agents 411 Photosensitizing Antiviralsmentioning
confidence: 99%
“…HSV-1 0.006 [469] gymnochrome B dengue 0.029 [475] hypocrellin A HSV-1 0.015 [469] hypocrellin B HSV-1 0.025 [469] 5-(perylen- virals (Section 3.2), but it was later shown that the compounds act as membrane-targeted photosensitizers [491][492][493]. Cationic imidazolyl and pyridyl porphyrins were characterized as promising photosensitizing antivirals against SARS-CoV-2 and HSV-1 [494,495]. A natural chlorine photosensitizer, pheophorbide a, inactivates HSV-1, HSV-2, MERS-CoV, SARS-CoV-2, YFV, HCV, and SINV, by targeting the lipid envelope [496,497] (Table 7).…”
Section: Disrupting Agents 411 Photosensitizing Antiviralsmentioning
confidence: 99%
“…Cationic 5,10,15,20-tetrakis( N -methylpyridinium-3-yl)-porphyrin (TMPyP3) is a positional isomer of TMPyP4 with similar chemical properties ( Figure 1 ). The addition of a long alkyl chain to tripyridylporphyrin resulted in antiviral effects and provided a model for photodynamic antimicrobial chemotherapy [ 13 ], while N -methylated and N -oxidized tripyridylporphyrins with long alkyl chains have shown strong PDT effects and inhibitory activity in sphingolipid metabolism, suggesting a potential for the treatment of cancerous cells [ 14 ]. While these results are encouraging, it is important to note that they were obtained in cell cultures, leaving the specificity in and effectiveness on tumors in an in vivo model unknown.…”
Section: Introductionmentioning
confidence: 99%